ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DEDICADA A LA PRODUCCIÓN Y COMERCIALIZACIÓN DE GRANOLA CON STEVIA EN LA CIUDAD DE LOJA. - AYALA ROBAYO, JESSICA ALEXANDRA (2018)
The present study contains the analysis oriented to the creation of a producer and marketer of granola with stevia in the city of Loja, with the aim of producing a natural product to contribute to the health of the inhabitants of the town. That is why you intend to perform the analyzes that are part of the investment project. For example, as merchants, service providers, service providers, etc. of the locality (offerors). The market study carried out on the population of the city of Loja was also determined, with a sample of 397 surveys, which helped determine the results: a potential demand of 3.315.897 corresponds to the granola units that can arrive a being consumed in the local market, an effective demand of 2.089.015 which is the units of granola that are consumed once they are installed in the market. In the same way, the balance of demand and supply was analyzed, with results obtained from the effective demand and the projection of the offer, thus establishing the unsatisfied demand with a total of 1,316.671 units of granola that were not acquired in the local market, considering that this amount is the artisanal production in the households of the population for its consumption. 7 A marketing plan was executed to define the scope possibilities that the product can have in the market in which it will be developed, considering positive and negative aspects. In the technical study, the macro and micro localization, size and engineering of the project, process diagrams, flowchart of times and movements, technical requirements such as machinery and equipment, furniture and fixtures were established. The administrative study was carried out, constituting the microenterprise as a limited liability company, and the organizational structure with hierarchical levels of the different areas through organization charts detailing the functions of each person that will be part of the company through the function manuals. The financial study established, the investment and the financing through the contribution of the partners and the bank loan, being these requirements necessary to start the project. The financial evaluation determined the feasibility of the project according to the following results: the VAN was obtained after measuring the flows of future income and expenses minus the initial investment, establishing a profit for the organization with a result of $ 60,098.32. , the TIR reflects the performance of the funds invested with an interest rate of 55.04%; the RB/C 8 makes a connection between the benefits and the costs of the project, which established that for every dollar invested a profit of thirty-four cents of American dollars is obtained, the PRC establishes that the time to recover the investment will be two years, seven months and six days; the sensitivity analysis served to make investment decisions, identifying those elements that are most sensitive to a variation, where the increase in costs was determined with 16.6321% and a decrease in revenues with 12.3871%. Then, it is indicated that the current project has profitability to take effect after the corresponding analyzes. Finally, the corresponding conclusions and recommendations for the research work are presented.